Linchpins empower promiscuous electrophiles to enable site-selective modification of histidine and aspartic acid in proteins. Issue 19 (19th April 2021) - Rawale, Dattatraya Gautam; Thakur, Kalyani; Sreekumar, Pranav; T. K., Sajeev; A., Ramesh; Adusumalli, Srinivasa Rao; Mishra, Ram Kumar; Rai, Vishal
Abstract : Linchpin-enabled promiscuous electrophile uncovers an unchartered reactivity landscape for the precision engineering of proteins. Abstract : The conservation of chemoselectivity becomes invalid for multiple electrophilic warheads during protein bioconjugation. Consequently, it leads to unpredictable heterogeneous labeling of proteins. Here, we report that a linchpin can create a unique chemical space to enable site-selectivity for histidine and aspartic acid modifications overcoming the pre-requisite of chemoselectivity.